The Strategy of Puppet Shadow Industry Development and Education Management Character Building Based in Manyaran Subdistrict Wonogiri - Supeni, Siti (Proceeding of International Conference on Teacher Training and Education, 2016)
Puppet is a perfoming art originally from Indonesia which fast developed in Java. The subdistcric Manyaran has puppet 56 home  industries of handycraft. The aims: (1) developing strategy in increasing social economy through bussiness character building, (2) analysis industry, (3) developing workshop of puppet industry character building based in increasing industrial works, by entrepreneurship in developing creative industry.Methods is descriptive qualitative, Need analysis is done by problem, potency and hope through FGD, and experimental method.The result is to develop  of puppet industry and bussiness management character building. based for entrepreneurcharacteristic  people  in doing management process 90% through home industry. It needs to be supported in order to not work in another field got 88%, all of the people have skills to be developed continuously 78%, the values of its production for welfare societ 81%. Government policy supported local lesson curricula at schools, 75%. In fact Junior and Senior High School have done it, 83%. Export marketing, tourism packages by touring from schools, 81%. The handcrafters really agree in their villages will be created as tourism village. The character building in entrepreneurship is done since early programed, it is necessary socialisation Grand Design of Charater Building strategy for puppet handcrafters 75%. Conclusion, in supporting the development of handcrafters character puppet industry should involve all components: (1) the content of the curriculum, (2) the procces of instruction,(3) the quality of relationships), (4) the handling of discipline,implementation activity of co-curicula at school, character education is the deliberate effort to help people understand, care about, and act upon core ethical value, and ethos in all puppet handcrafters social environment.